How Private Creditors Fared in Emerging Debt Markets, 1970-2000 - Zettelmeyer, Jeromin; Klingen, Christoph; Weder, Beatrice (Washington, D.C. : International Monetary Fund, 2004)
We estimate ex post returns to emerging market debt by combining secondary-market prices with observed flows based on World Bank data. From 1970-2000, returns averaged 9 percent per annum, about the same as returns on a ten-year U.S. treasury bond. This reflects the combined effect of the 1980s debt crisis and much higher returns during 1989-2000. Annual returns since 1986 have been less volatile than emerging market equity returns but more volatile than returns on U.S. corporate or high-yield bonds. However, unlike returns on these bonds, emerging market debt returns do not seem significantly correlated with U.S. or world stock markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet